Adaptation to Poverty in Long-Run Panel Data - Clark, Andrew E.; D’Ambrosio, Conchita; Ghislandi, Simone (The Review of Economics and Statistics, 2016)
We consider the link between poverty and subjective wellbeing and focus in particular on potential adaptation to poverty. We use panel data on almost 54,000 individuals living in Germany from 1985 to 2012 to show, first, that life satisfaction falls with both the incidence and intensity of contemporaneous poverty. We then reveal that there is little evidence of adaptation within a poverty spell: poverty starts bad and stays bad in terms of subjective well-being. We cannot identify any cause of poverty entry that explains the overall lack of poverty adaptation.